2016
DOI: 10.1111/pedi.12377
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional view of the current state of treatment of youth with type 2 diabetes in the USA: enrollment data from the Pediatric Diabetes Consortium Type 2 Diabetes Registry

Abstract: Frequency of insulin therapy in youth with T2D was associated with increased disease duration and those with longer duration rarely achieve target HbA1c level. This highlights the aggressive course of T2D in youth and adolescents. Additionally, co-morbidities are not being adequately treated. Follow up data from the PDC will provide additional important information about the natural history of T2D and patterns of gaps in treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 22 publications
0
45
0
Order By: Relevance
“…These findings support a recent report that lower HbA1c levels at the time of diagnosis strongly predicts durable control with metformin monotherapy in T2D youth . In addition, prior PDC data reporting that, in youth who fail metformin monotherapy, insulin rarely lowers HbA1c levels to target values <7.5% supports the importance of early diagnosis of T2D in youth …”
Section: Discussionmentioning
confidence: 99%
“…These findings support a recent report that lower HbA1c levels at the time of diagnosis strongly predicts durable control with metformin monotherapy in T2D youth . In addition, prior PDC data reporting that, in youth who fail metformin monotherapy, insulin rarely lowers HbA1c levels to target values <7.5% supports the importance of early diagnosis of T2D in youth …”
Section: Discussionmentioning
confidence: 99%
“…In addition, lipid profile data were available for only 39% of the participants. In a previous analysis from the PDC, we reported that HTN was associated with higher BMI ( p < 0.001), dyslipidemia with higher HbA 1c ( p < 0.001), and microalbuminuria with longer diabetes duration ( p = 0.001) [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, blood pressure (BP) percentiles adjusted for age, gender, and height were calculated from the CDC charts [10]. As reported earlier [11], hypertension (HTN) was defined as a medical problem noted in the medical record as not resolved, currently being treated for HTN at enrollment, or a systolic or diastolic BP measurement ≥95th percentile for those aged <18 years and systolic BP ≥140 or diastolic BP ≥90 mm Hg for those aged ≥18 years within 28 days of enrollment. BP data were available for 268 out of 276 patients.…”
Section: Methodsmentioning
confidence: 99%
“…The TODAY study also demonstrated that metformin monotherapy fails to maintain glycated hemoglobin (HbA1c) <8.0% (<64 mmol/mol) in most adolescents during the second year of treatment, even in the face of substantial residual endogenous insulin . Furthermore, the SEARCH for Diabetes in Youth Study demonstrated that more than one‐quarter (27%) of youth with T2D participating in that study had poor glycemic control with HbA1c ≥9.5% (≥80 mmol/mol), and the Pediatric Diabetes Consortium T2D Registry has shown that rescue therapy with insulin, in metformin treatment failures, rarely lowers HbA1c to <7.5% (<58 mmol/mol), the target level recommended by the American Diabetes Association and the International Society for Pediatric and Adolescent Diabetes. Nevertheless, metformin and insulin remain the only pharmacologic agents approved for use in youth with T2D below 18 years of age, underscoring the need for new therapies.…”
Section: Introductionmentioning
confidence: 99%